Implementing the 3T‐approach for cervical cancer screening in Cameroon: Preliminary results on program performance - Juliette Levy; Marie dePreux; Bruno Kenfack; Jessica Sormani; Rosa Catarino; Eveline F. Tincho; Chloé Frund; Jovanny T. Fouogue; Pierre Vassilakos; Patrick Petignat (Cancer Medicine)
Abstract Option recommended by World Health Organization (WHO) includes human papillomavirus (HPV) primary screening followed by visual inspection with acetic acid (VIA) triage. We implemented a program based on a 3T‐approach (Test‐Triage and Treat). Our objective was to verify the effectiveness of the program by defining a set of performance indices. A sensitization campaign was performed in Dschang (Cameroon) and women aged 30‐49 years were invited to participate for screening based on the 3T‐approach. Participants performed HPV self‐sampling (Self‐HPV), analyzed with the point‐of‐care Xpert HPV assay followed by VIA/VILI triage and treatment if required. Key performance indicators (KPIs) for screening, diagnosis, treatment and follow‐up were defined, and achievable targets were described for which the approach is likely to be running optimally. A total of 840 women with a mean age of 39.4±5.9 years participated. The KPIs included (i) the screening rate (8.4% at 7 months, target =20% at 12 months), (ii) HPV positivity rate (19.8%, expected range 18‐25%), (iii) compliance to referral to VIA/VILI and complete test (100%, target >90%), (iv) compliance to referral to thermal ablation (100%, target >90%), (v) VIA/VILI positivity rate (50.6%, expected range 45‐55%), (vi) a single visit from diagnostic to treatment (79.8%, target >80%), (vii) compliance to follow‐up at 1 month (96.4%, target >80%) and (viii) at 6 months (70.6%, target >80%). Program performance based on the single‐visit 3T‐approach corresponded to defined targets and preliminary results support adequateness of KPIs for periodic monitoring.